Sustainable financial markets: Financial transaction tax and high capital buffers indispensable - Dorothea Schäfer (DIW Economic Bulletin, 2013)
The sustainability of the financial markets is a requirement that has only appeared on the economic policy agenda very recently, whereas a stable financial system has been a declared goal for decades. The relationship between sustainability and stability is, however, still unclear. The two terms are often used synonymously but stability is only one part of sustainability. The following outlines the requirements for sustainable financial markets based on the current general principles of environmental sustainability. Financial stability is considered a public good. The prerequisites for the sustainability of financial markets include internalizing costs of use, financial institutions forming adequate buffers in order to restore stability autonomously and without the help of the taxpayer, diversity, a longterm outlook, and credibility. Financial transaction tax and a higher leverage ratio meet the requirements for sustainability of financial markets; both are cornerstones of the planned restructuring of the financial markets.
Keywords: G20; 330; sustainable financial architecture; financial transaction tax; leverage ratio